1988
DOI: 10.1002/ajmg.1320310320
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal detection of 46,XY,rec(5),dup q, inv(5)(p13q33) using DNA analysis, flow cytometry, and in situ hybridization to supplement classical cytogenetic analysis

Abstract: Distinguishing between balanced and unbalanced chromosome complements segregating from parental rearrangements may be difficult using only classical cytogenetic techniques if banding morphology is similar under both expectations. In these situations, supplementing cytogenetic analysis with molecular genetic techniques and flow cytometry may provide increased diagnostic accuracy. To illustrate this, we present a case in which similar band pattern morphology would be expected for both the balanced carrier (heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Epstein (1986) suggested that the effects of double segmental aneuploidy could be classified into the following three general categories: 1) one in which the phenotype derives completely or almost completely from that of one of the segmental aneuploidies; 2) one characterized by the presence of some of the features of each of the contributing imbalances; 3) those cases in which the phenotype is a reasonable composite of the individual segmental aneuploid phenotype. Since all the patients excluding two cases (Schroeder et al, 1986;Martin et al, 1988), as well as our case, showed clinical features of partial monosomy 5p and partial trisomy 5q, this double segmental aneuploidy can be classified as a third composite phenotype category which was termed by Carlin and Norman (1978) as a "phenotype hybrid." Among the features noted in our case, severe and complex heart abnormalities, and inguinal hernia were occasioned by partial trisomy 5q, whereas the cat-like cry and dermatoglyphics were presumed to caused by partial monosomy 5p (Beemer et al, 1984).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Epstein (1986) suggested that the effects of double segmental aneuploidy could be classified into the following three general categories: 1) one in which the phenotype derives completely or almost completely from that of one of the segmental aneuploidies; 2) one characterized by the presence of some of the features of each of the contributing imbalances; 3) those cases in which the phenotype is a reasonable composite of the individual segmental aneuploid phenotype. Since all the patients excluding two cases (Schroeder et al, 1986;Martin et al, 1988), as well as our case, showed clinical features of partial monosomy 5p and partial trisomy 5q, this double segmental aneuploidy can be classified as a third composite phenotype category which was termed by Carlin and Norman (1978) as a "phenotype hybrid." Among the features noted in our case, severe and complex heart abnormalities, and inguinal hernia were occasioned by partial trisomy 5q, whereas the cat-like cry and dermatoglyphics were presumed to caused by partial monosomy 5p (Beemer et al, 1984).…”
Section: Discussionmentioning
confidence: 64%
“…So far, six cases in four families (Faed et al, 1972;Ebbin et al, 1979;Beemer et al, 1984;Schroeder et al, 1986) and one fetus (Martin et al, 1988) with partial monosomy 5p and trisomy 5q due to parental pericentric inversion of chromosome 5 have been reported (Table l). Epstein (1986) suggested that the effects of double segmental aneuploidy could be classified into the following three general categories: 1) one in which the phenotype derives completely or almost completely from that of one of the segmental aneuploidies; 2) one characterized by the presence of some of the features of each of the contributing imbalances; 3) those cases in which the phenotype is a reasonable composite of the individual segmental aneuploid phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For chromosomes 14,15,18,19,21,22, and the Y chromosome, the contribution of biological variation to the total variation of HO and/or CA fluorescence is more evident (Table 3). Nevertheless, for most chromosomes our results on the total variation in peak positions are in agreement with the variation in peak position and chromosome length, obtained in other flow cytometric and cytogenetic studies (9,11,24,29).…”
Section: Sources Of Variation In Bivariate Flow Karyotypingmentioning
confidence: 99%
“…Bivariate flow karyotyping of human chromosomes has proven to be a helpful tool in the cytogenetic study of congenital and other diseases (1, 2, 5, 9, 14,16,17,24). It can be used to detect several types of aberrations: (1) numerical changes, (2) most nonreciprocal translocations, (3) most reciprocal translocations that exchange different length chromosome segments or equal size segments with different quantities of HO and CA bands, and (4) chromosomal deletions or inse tions.…”
mentioning
confidence: 99%